CXCL12 Mediates Aberrant Costimulation of B Lymphocytes in Warts, Hypogammaglobulinemia, Infections, Myelokathexis Immunodeficiency - Roselli, Giuliana; Martini, Elisa; Lougaris, Vassilios; Badolato, Raffaele; Viola, Antonella; Kallikourdis, Marinos (Frontiers in Immunology, 2017)
The WHIM (Warts, Hypogammaglobulinemia, Infections, Myelokathexis) syndrome is an immunodeficiency caused by mutations in chemokine receptor CXCR4. WHIM patient adaptive immunity defects remain largely unexplained. We have previously shown that WHIM-mutant T cells form unstable immunological synapses, affecting T cell activation. Here we show that, in WHIM patients and WHIM-CXCR4 knock-in mice, B cells are more apoptosis-prone. Intriguingly, WHIM-mutant B cells were also characterized by spontaneous activation. Searching for a mechanistic explanation for these observations, we uncovered a novel costimulatory effect of CXCL12, the CXCR4 ligand, on WHIM-mutant but not wild-type B cells. The WHIM-CXCR4-mediated costimulation led to increased B cell activation, possibly involving mTOR, albeit without concurrently promoting survival. A reduction in antigenic load during immunization in the mouse was able to circumvent the adaptive immunity defects. These results suggest that WHIM-mutant CXCR4 may lead to spontaneous aberrant B cell activation, via CXCL12-mediated costimulation, impairing B cell survival and thus possibly contributing to the WHIM syndrome defects in adaptive immunity.